State-legal regulation of self-employment in the Republic of Kazakhstan - Azatbek, T.A.; Baytenizov, D.T.; Dubina, I.N. (BUKETOV BUSINESS REVIEW, 2017)
The article is devoted to the problem of formation of productive self-employment in Kazakhstan. Head of State N.Nazarbayev, having proclaimed the idea of the «Universal Labor Society» in 2012, always emphasizes the need for worthy payment of this labor and creation of conditions and opportunities for employment of unemployed people. In order to stimulate the development of self-employment, the state provides this type of activity with appropriate regulatory and legal regulations, and also adopts programs aimed at the realization of productive employment. Since gaining independence, the system of state regulation in the sphere of employment in Kazakhstan has passed several stages of its formation and at the present stage a legislative base has been formed in the sphere of self-employment corresponding to the analogues of the leading countries of the world. The authors in their work analyzed the available mechanisms and tools for the development of self-employment. The authors pay particular attention to the analysis of the concept of self-employment and its forms, presented in legislative acts, which are the basis for effective regulation by the state.The article presents the conclusions and recommendations of the authors on upgrading the infrastructure for the development of self-employment, as well as measures to stimulate productive self-employment.